Coordinating forest tenure reform: Objectives, resources and relations in Indonesia, Kenya, Nepal, Peru, and Uganda - Rodd, M.; Fisher, M.; Monterroso, I.; Liswanti, N.; Maryudi, A.; Larson, A.M.; Mwangi, E.; Herawati, T. (Elsevier, 2022)
As forest tenure reform is mainstreamed around the world, outcomes are increasingly determined by the institutions that are responsible for administering its operationalisation and translating policy into implementation. This global study examines state institutional contexts of tenure reform in Kenya, Uganda, Nepal, Indonesia, and Peru. Interviews were administered in 2016–2017 using a fixed questionnaire applied across all countries involving 26–32 respondents from state implementers of forest tenure reform in each country for a total of 145 respondents. Although our study engagement was tailored for specific country contexts, we identified generalisable forest tenure reform trends through comparative analysis. Findings situate the overall bridging role that state institutions play in forest tenure reform, which we describe as falling under three key overarching coordination functions, namely: coordination among implementers, coordination of objectives, and coordination of resources. These three categories provide insights not only for gauging the progress of a country's forest tenure reform, but also for evaluating how robust reforms have been, and where forest tenure reforms are headed in the future.